Pengaruh Pengaruh Literasi Keuangan, Locus Of Control Dan Kepribadian Terhadap Perilaku Keuangan Melalui Financial Self-Efficacy Sebagai Variabel Intervening (Business and Accounting Education Journal, 2022)
This study aims to analyze the effect of financial literacy, locus of control and personality on financial behavior directly or indirectly through financial self-efficacy. The research population was students of Economics Education, Faculty of Economics, Semarang State University, class of 2018, with a total of 262 students. Methods of data collection using a questionnaire. Data analysis techniques using descriptive statistical analysis, path analysis and sobel test. The results showed that (1) financial literacy, locus of control, personality, and financial self-efficacy had a positive and significant effect on financial behavior, (2) personality had no effect on financial behavior, (3) financial literacy and locus of control has a positive and significant effect on financial self-efficacy, (4) the results of the mediating effect of financial literacy and locus of control have a significant positive effect on financial behavior.